Fish Bone Induced Hepatic Abscess : A Rare Case - Adil Khan; Vivek Bhardhan; Aswini Kumar Sahoo (JK Science)
Pyogenic liver abscess usually presents with fever with chills and rigor, jaundice and pain abdomen. Hepatic abscess due to foreign body perforation at GI tract are extremely rare. We report a case of fish bone ingestion causing stomach perforation which lead to hepatic abscess and patient was successfully treated with antibiotics and percutaneous drainage with foreign body left in situ.